Evaluating Brine Deposits Using Borehole Magnetic Resonance. Issue 1 (1st December 2018) - Lloyd, Adam; Hopper, Tim; Neville, Tom; Birt, Benjamin
Abstract : Brine mining is an important source of elements such as potassium, iodine, lithium, and bromine that occur in solution in groundwater, typically in shallow brines occurring beneath saline or dry lakes or in deep brines in sedimentary basins. Where feasible, brine mining is an attractive alternative to conventional mining due to lower surface and environmental impact and lower OPEX than conventional mining operations. As with any resource, evaluating brine deposits requires developing an understanding of how much resource is present and how it can be most economically produced. How much resource is present is a function of the bulk aquifer volume, the specific yield, and the brine composition, while the primary subsurface control on economic production is hydraulic conductivity, which dictates the rate at which the brine can be produced to surface. Specific yield and hydraulic conductivity are analogous to the free fluid volume and permeability quantities that are of interest in oil and gas resource assessment. Borehole magnetic resonance has been applied in the oil and gas industry for the evaluation of bound and free fluid volumes and permeability for over twenty years. These same methodologies are equally applicable in the evaluation of brine deposits, however the hypersaline brines that are targets for commercial development cause highly conductive borehole environments that can be extremely challenging for magnetic resonance measurements. Nevertheless, use of borehole magnetic resonance measurements to help evaluate a sulphate of potash brine deposit currently under assessment shows that such measurements can be employed successfully in these environments.